2019
DOI: 10.3390/pr8010024
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Kernel Methods for Feature Extraction in Nonlinear Process Monitoring

Abstract: Kernel methods are a class of learning machines for the fast recognition of nonlinear patterns in any data set. In this paper, the applications of kernel methods for feature extraction in industrial process monitoring are systematically reviewed. First, we describe the reasons for using kernel methods and contextualize them among other machine learning tools. Second, by reviewing a total of 230 papers, this work has identified 12 major issues surrounding the use of kernel methods for nonlinear feature extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 322 publications
0
48
0
Order By: Relevance
“…We further note that the performance of the NARX can be improved in these experiments by training it with more data than just 1001 samples. The kernel-based SIMs, on the other hand, may become too slow for prediction when trained with larger data sets [41]. Nevertheless, our proposed FR-MKCVA is intended for scenarios where training data has a moderate sample size but is high-dimensional.…”
Section: Fr-mkcva: Testing Phasementioning
confidence: 99%
See 1 more Smart Citation
“…We further note that the performance of the NARX can be improved in these experiments by training it with more data than just 1001 samples. The kernel-based SIMs, on the other hand, may become too slow for prediction when trained with larger data sets [41]. Nevertheless, our proposed FR-MKCVA is intended for scenarios where training data has a moderate sample size but is high-dimensional.…”
Section: Fr-mkcva: Testing Phasementioning
confidence: 99%
“…For these scenarios, we have shown that certain improvements in the kernel design can produce better kernel-based SIMs. This calls for more research into kernel design in the future, such as exploring deep and ensemble kernel architectures [41]. By improving model generalization ability, industrial activities that depend on these models can perform better.…”
Section: Fr-mkcva: Testing Phasementioning
confidence: 99%
“…In addition, FGMM-BIP index also uses the Bayesian inference technique and a unified monitoring indicator, similar to the FKF. PCAbased T 2 and SPE are extensively applied to detecting faulty operation in process industries [31].…”
Section: Comparison Studymentioning
confidence: 99%
“…Among the kernel-based methods, KPCA is a powerful technique, widely applied in process monitoring and fault diagnosis [1], [3], [39]- [41]. However, the commonly used Gaussian radial basis function (RBF) may suffer from overfitting problem, due to its lack of extrapolation ability, particularly while an inappropriate kernel width is selected [28], [42], [43]. The combination of RBF and polynomial kernels can provide enhanced modeling performance [44].…”
Section: Introductionmentioning
confidence: 99%